Annual Plan 1999-2000 State Planning Board Thiruvananthapuram - Planning Commission (Planning Commission, 1999)
The approved plan outlay for the State's Ninth Five-Year Plan (1997-2002) is Rs. 16100 crores with the major objective of achieving a growth rate of 7 per cent per annum during the plan period. The outlays for the first two years of the Ninth Plan, viz. 1997-98 and 1998-99, were Rs.2855 crores and Rs.3100 crores respectively. For 1999-2000 the outlay is fixed at Rs.3250 crores. The Broad sector wise allocation is given below.
State Planning Board